2011
DOI: 10.1038/bjc.2011.178
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system failure in melanoma patients: results of a randomised, multicentre phase 3 study of temozolomide- and dacarbazine- based regimens

Abstract: Background:This study compared the central nervous system (CNS) metastasis incidence between a temozolomide- and a dacarbazine-based regimen in untreated stage IV melanoma patients.Methods:A total of 150 patients were randomly assigned to receive either oral temozolomide (200 mg m−2 per day; days 1–5) or intravenous dacarbazine (800 mg m−2; day 1), in combination with intravenous cisplatin (75 mg m−2; day 1) and subcutaneous interleukin-2 (3 MU twice daily; days 9–18), every 28 days (CTI and CDI).Results:A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 23 publications
5
33
0
2
Order By: Relevance
“…Die Kombination Fotemustin plus WBRT verzögerte im Vergleich zu Fotemustin allein in einer Phase-III-Studie mit 76 Melanompatienten mit Hirnmetastasen zwar signifikant die zerebrale Progression, allerdings ohne dass die Kombination einen signifikanten Einfluss auf das objektive Ansprechen und das Gesamtüberleben hatte [17]. Das Auftreten von Hirnfiliae scheint sich bei Melanompatienten durch liquorgängige Medikamente zu verzögern: Fotemustin und Temozolomid (jeweils vs. Dacarbazin) verlängerten die Zeit bis zur Hirnmetastasierung [18,19]. …”
Section: Paradigmenwechsel In Der Therapie Von Hirnmetastasen Beim Meunclassified
“…Die Kombination Fotemustin plus WBRT verzögerte im Vergleich zu Fotemustin allein in einer Phase-III-Studie mit 76 Melanompatienten mit Hirnmetastasen zwar signifikant die zerebrale Progression, allerdings ohne dass die Kombination einen signifikanten Einfluss auf das objektive Ansprechen und das Gesamtüberleben hatte [17]. Das Auftreten von Hirnfiliae scheint sich bei Melanompatienten durch liquorgängige Medikamente zu verzögern: Fotemustin und Temozolomid (jeweils vs. Dacarbazin) verlängerten die Zeit bis zur Hirnmetastasierung [18,19]. …”
Section: Paradigmenwechsel In Der Therapie Von Hirnmetastasen Beim Meunclassified
“…Chiarion-Sileni et al . [22], in a phase III randomized study, showed the inefficacy of temozolomide in preventing CNS metastasis from melanoma, although they suggested that temozolomide may delay the onset of CNS disease. In the present study, the median time to CNS involvement was only 5.33 months, which undermines that claim.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of temozolomide in comparison with dacarbazine in the treatment of patients with advanced metastatic malignant melanoma Complete response: The summary of RR for complete response of temozolomide in comparison with dacarbazine in patients with advanced metastatic malignant melanoma for three included trials [11][12][13] was 0.83 (95% CI = 0.26-2.64), which was nonsignificant (P = 0.76; Fig. 2a).…”
Section: Efficacymentioning
confidence: 96%